Analisis Pemanfaatan Marketplace SIAKU Untuk Meningkatkan Penjualan UMKM di Provinsi Riau - Nugraha, M Yusuf; Sumarno, Sumarno; Mujiono, Mujiono (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the use of the SIAKU marketplace in increasing sales of Micro, Small, and Medium Enterprises (MSMEs) in Riau Province. The SIAKU Marketplace is a digital platform developed to help MSMEs market their products more widely. This study uses a quantitative approach with a time series method based on secondary data on the number of products and transactions registered in the SIAKU marketplace during 2023 to 2024. The results of the study show an increasing trend in the number of products and transactions in certain periods, especially in the middle and end of the year, which is influenced by seasonal factors, promotions, and support from government programs such as routine provision of MSME products through LKPP. However, there are still fluctuations in certain months which indicate the need for a more consistent promotional strategy and continued support for MSMEs. Overall, SIAKU has proven to have the potential to be an effective means of supporting the growth of MSME sales in the Riau region.